1996
DOI: 10.1007/s002280050144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mefloquine alone and with alcohol on psychomotor and driving performance

Abstract: Mefloquine did not impair driving performance but rather improved it in the longer test, suggesting that the drug may possess psychostimulating properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 6 publications
3
40
0
Order By: Relevance
“…It has also proven sensitive to many sedating agents including alcohol in blood concentrations as low as 0 . 035 g/dl (Ramaekers et al, 1992;Vuurman et al, 1996).…”
Section: Methodsmentioning
confidence: 97%
“…It has also proven sensitive to many sedating agents including alcohol in blood concentrations as low as 0 . 035 g/dl (Ramaekers et al, 1992;Vuurman et al, 1996).…”
Section: Methodsmentioning
confidence: 97%
“…On-the-road studies have reported residual impairment as long as 8 to 16 hours after intake of 7.5 mg zopiclone 9,28 and impaired performance for BAC as low as 0.035%. 29 In our study, we had a mean BAC of 0.035% between 3.5 and 6.5 hours after intake. Blood zopiclone concentrations were not measured in those real-driving studies, but most likely, the blood zopiclone concentrations in those studies were lower than the concentrations we measured 6.5 hours after intake of 10 mg zopiclone (20 Kg/L).…”
Section: Kuitunen Et Almentioning
confidence: 98%
“…We identified 37 trials of mefloquine chemoprophylaxis carried out between 1970 and 1997, of which 10 met the inclusion criteria 19 20 21 22 23 24 25 26 27 28 29 30 31. The 1 summarises the characteristics of these 10 trials, two of which are currently unpublished 24 28.…”
Section: Resultsmentioning
confidence: 99%